La técnica del ROLE PLAY y su influencia en la producción oral del idioma inglés en los estudiantes del cuarto grado “E" del nivel secundario de la l.E "Santa Rosa " Tarapoto • 2010 - Ruiz Ruiz, Juanita Veronica (2013)
The current investigation titled: LA TÉCNICA DEL ROLE PLAY Y SU FLUENCIA EN LA PRODUCCIÓN ORAL DEL IDIOMA INGLÉS EN LOS ESTUDIANTES DEL CUARTO GRADO “E” DEL NIVEL SECUNDARIO DE LA l.E *SANTA ROSA", deals of the study done to a sample of 27 pupils to obtain the aims proposed in the investigation. The investigation manifests the importance of the Role Play technique in the development of the oral production of the English language in the students at the secondary level of the educative institution "Santa Rosa" it contributes so that this capability is improved through this technique. For the achievement of the aims was necessary to create a new Lesson Plan that was adapted to the requirements of the investigation , which we call " Speaking in English", also different instruments of investigation are created that helped us to obtain a record of results for the database, such as: A pre-test, post-test, observation sheet of the oral production and observation sheet of the Role Play technique. These instruments helped us to demonstrate and put in evidence that the level of production of the English language through Role Play technique in the students secondary level of the educative institution "Santa Rosa" is good.